Improving Rotary Draw Bending Process by Changing a Geometry of the Pressure Bar - Řiháček, Jan; Peterková, Eva; Císařová, Michaela (Manufacturing Technology Journal, 2021)
The paper is focused on an analysis and optimization of the rotary draw benging process to eliminate bent tube ovality by modification of the pressure bar geometry. The bending process is realized on WafiosCNC bending machine. A tube that is bent for an automotive application is made of 34MnB5 steel. Currently, after tube bending process by an angle of 120°, an unacceptable ovality occurs. Therefore, it is necessary to improve the quality of production and thus prevent the formation of unacceptable ovality. In this case, the optimization of the pressure bar geometry is performed. For this reason, a numerical simulation using finite element method in ANSYS software is performed. Before the actual optimization, an accuracy of the simulation is verified by analysing of the current state and comparing it with simulation results.
Keywords: FEM; numerical simulation; ANSYS; 34MnB5 steel; tube bending